Potential Use Of Light Color Traps In Rice Powder Pest Control (Sitophilus oryzae L.) - Jusuf Manueke (Jurnal Agroekoteknologi Terapan, 2022)
The aim of the study was to determine the potential use of colored light traps as an effective and environmentally friendly method of controlling the rice powder pest Sitophilus oryzae L. The study used a completely randomized design (CRD) with 5 treatments and 3 replications. As a treatment in this research is the type of LED light color trap, namely A = white light trap; B = red light trap; C = blue light trap; D = yellow light trap; E = green light trap; and F = Control (trap without light). The test insects used were in the imago stage and the population of the test insects used was 150 individuals.Â  The results showed that the white light trap type population had the highest population of imago rice powder pests of S. oryzae trapped at 52.33 individuals (34.88%), followed by yellow light traps at 37.0 individuals (24, 67%), blue light traps are 24.0 individuals (16%), green light traps are 20.0 individuals (13.33%), and the lowest is red light traps is 13.33 individuals ( 8.88%. Incandescent light traps have the potential to be used in controlling rice powder pests of S. oryzae, especially white and yellow traps.Keywords: Environmentally friendly pest control; Light color traps; Rice powder pest Sitophilus oryzae L.